Investigating Aspects of Personal and Social Identity of Individuals with Vision Disability - Ρήγα, Αικατερίνη; Αργυρόπουλος, Βασίλης (Education Sciences, 2025)
It seems that in recent years, the field of Social Sciences put great emphasis on research which deals with issues pertinent to aspects of personal and social identity. According to relevant research, the development of personal identity determines the self-identification of the individuals, whereas the individuals’ social identity is mutually dependent on their participation and integration in social events and activities. However, there are specific population groups, such as individuals with vision disability, whose personal and social identity has not been adequately investigated in relevant Greek literature, a fact that contributes to maintaining a vague picture regarding the challenges they face in terms of self-concept and their integration into the broader social context. The present study aims to identify and analyze the ways in which individuals with vision disability perceive their personal and social identity. For this purpose, a critical literature review was conducted, through which it may be conjectured that visual impairment is still treated and interpreted according to the principles of the medical paradigm, which means that individuals with vision disability struggle to manage an extremely difficult situation on a personal level due to their blindness. This situation, according to the above model, creates difficulties in developing their personal identity, with negative consequences for their full integration into the broader social context. Lastly, the present study also discusses the social paradigm of disability, which serves as a counterpoint in understanding and interpreting disability and in shaping frameworks concerning both personal and social identity.